Consequence management for minimising financial mismanagement in the City of Johannesburg Metropolitan Municipality - Fourie, D.J. (David Johannes) (University of Pretoria, 2026)
Dissertation (MAdmin (Public Management and Policy))--University of Pretoria, 2024.